Implementing Enterprise Cybersecurity with Opensource Software and Standard Architecture - Handa, Anand (River Publishers, 2021)
This book describes multiple projects which can help in developing cybersecurity solution architectures and the use of the right tools from the open-source software domain. These projects are covered in detail with recipes on how to use open-source tooling to obtain standard cyber defense and the ability to do self-penetration testing and vulnerability assessment.